Temperature Dependent of The Forbidden Energy Gap of GaSb Grown by MOCVD - Agus Subekti (Jurnal Matematika & Sains, 2000)
This work reports on the investigation of the temperature dependent of the forbidden energy gap of GaSb. The GaSb samples were grown by MOCVD technique using trimethylgallium (TMGa) and trimethylantomony (TMSb) as the precursors. The temperature dependent of the energy gap was obtained from a plot of the square of absorption coefficient versus photon energy at temperature range of 10-300K follows the equation , wich in good agreement with results previously reported in the literatures.